Leaning against house prices: A structural VAR investigation - Luca Benati (University of Bern, Department of Economics, 2020)
Evidence from monetary VARs suggests that in the U.S., Canada, and the U.K. 7 the impact of monetary shocks on real house prices is about three to five times as large 8 as that on real GDP. Although these trade-offs are not manifestly unfavorable, in the 9 light of the large differences in the magnitudes of house prices and GDP fluctuations, a 10 monetary policy of leaning against the former would inevitably entail significant losses 11 in the latter. I use the identified VARs in order to explore the corresponding trade12 offs associated with a monetary policy of weakly, but systematically leaning against 13 house prices. Results from 'modest' (in the sense of Leeper and Zha, 2003) policy counterfactuals suggest that, in 1 population, the impact on real house prices is about 2 three times as large as that on real GDP for all of the three countries. Within the 3 specific context of the upsurge in U.S. house prices which pre-dated the financial crisis, 4 a shortfall of one per cent of GDP would have been associated with a decline in real 5 house prices by about four per cent.
Keywords: E30; E32; 330; Structural VARs; house prices; sign restrictions; zero restrictions